Science Fun: Theory of Optics - Eka Desiriah; Nurul Afifah; Jelita Puspita Ningrum Choirunnisa (Studies in Philosophy of Science and Education, 2020)
We, as budding researchers, try to present science in the form of comics. We present the theory of optics by Christiaan Huygens and Sir Isaac Newton in a short comic strip. As we know, the Huygens principle explains that each wavefront can be considered to produce new wavelets or waves with the same wavelength as the previous one. A wavelet can be likened to a wave generated by a rock dropped into the water. The Huygens principle can be used to explain the diffraction of light in small slits. When passing through a small gap, the wavefront will create an infinite number of new wavelets so that the waves do not just flow straight, but spread out. By doing so, Huygens discovered his telescope. In this paper, we then illustrate his telescope through a simple comic.